Effects of infliximab therapy on transmural lesions as assessed by magnetic resonance enteroclysis in patients with ileal Crohn's disease - Van Assche, Gert; Herrmann, Karin A; Louis, Edouard; Everett, Simon M; Colombel, Jean-Frédéric; Rahier, Jean-François; Vanbeckevoort, Dirk; Meunier, Paul; Tolan, Damian; Ernst, Olivier; Rutgeerts, Paul; Vermeire, Séverine; et al. (Journal of Crohn's and colitis, 2013)
Anti TNF therapy induces mucosal healing in patients with Crohn's disease, but the effects on transmural inflammation in the ileum are not well understood. Magnetic resonance-enteroclysis (MRE) offers excellent imaging of transmural and peri-enteric lesions in Crohn's ileitis and we aimed to study its responsiveness to anti TNF therapy. In this multi-center prospective trial, anti TNF naïve patients with ileal Crohn's disease and with increased CRP and contrast enhanced wall thickening received infliximab 5 mg/kg at weeks 0, 2 and 6, and q8 weeks maintenance MRE was performed at baseline, 2 weeks and 6 months and assessed based on a predefined MRE score of severity in ileal Crohn's Disease. Twenty patients were included; of those, 18 patients underwent MRE at week 2 and 15 patients at weeks 2 and 26 as scheduled. Inflammatory components of the MRE index decreased by ≥2 points and by ≥50% at week 26 (primary endpoint) in 40% and 32% of patients (per protocol and intention to treat analysis, respectively). The MRE index improved in 44% at week 2 and in 80% at week 26. Complete absence of inflammatory lesions was observed in 0/18 at week 2 and 13% (2/15) at week 26. The obstructive elements did not change. Clinical and CRP improvement occurred as early as wk 2, but only CDAI correlated with the MRE index. Improvement of MRE occurs from 2 weeks after infliximab therapy onwards and correlates with clinical response but normalization of MRE is rare.